Organizational Commitment and the Readiness towards Accrual Accounting: The Moderating Role of Job Satisfaction - Alghizzawi, Moawiah Awad; Masruki, Rosnia Binti (International Journal of Asian Social Science, 2019)
The government of Jordan has recently begun preparing to transition towards accrual accounting. However, this process is accompanied by many obstacles that might prevent its proper adoption. Therefore, there is a need to create readiness among the government servants to ensure successful adoption of the new accounting system. As such, this study intends to examine the readiness of Jordanian government servants in the process of transition towards accrual accounting. Besides that, this study intends to examine two possible factors that may affect the readiness of Jordanian government servants, which are: (i) the effect of organizational commitment and (ii) the moderating role of job satisfaction. Questionnaires were distributed to 331 Jordanian government servants in the Ministry of Finance (MOF) and the departments belonging to it. The results indicated that the government servants are ready to transition towards accrual accounting and inclined to accept the change. In addition, organizational commitment positively affects the readiness of government servants, and job satisfaction positively moderates the relationship. Finally, some limitations were considered in this study.